The Cytotoxic T-Lymphocyte Epitope of the Plasmodium falciparum Circumsporozoite Protein Also Modulates the Efficiency of Receptor-Ligand Interaction with Hepatocytes - Rathore, Dharmendar (American Society for Microbiology, 2000)
Malaria sporozoites are transmitted from the mosquito salivary gland to host hepatocytes within minutes of an infectious bite. The circumsporozoite protein (CS), which covers the surface of Plasmodium sporozoites, functions during these minutes in the targeting of host liver cells. The protein's potentially important role in an antimalaria vaccine has spawned interest in both the host immune responses to the parasite's presence and the actual functional role of the protein in the targeting of host liver cells. Here we show that the region of CS known to elicit a cytotoxic T-lymphocyte (CTL) response to irradiated sporozoites also, somewhat ironically, mediates the receptor-ligand interaction essential to parasite invasion of the host. Hence, the structure of CS represents a balance of potentially counterdirectional forces. Polymorphism in the CTL epitope appears to be a product of this balanced state as opposed to an “arms race” as it is so often portrayed. The conceptual difference between the theories regarding the maintainance of polymorphism in CTL epitopes may have significant implication for vaccine design.